The Effect Of Task Based Flipped Classroom On Students’ Perceived Engagement And Performance In Narrative Essay Writing Among Cambodian High School Students - Sanhei, Nhor (2023)
This study examines the effect of task-based flipped classrooms using video-based instruction on perceived engagement and writing performance for narrative essay writing among Cambodian high school students. Two modes of instruction, flipped classroom without tasks (FCoT) and flipped classroom with tasks (FCT), were applied for this purpose, where engagement was also evaluated based on perceived behavioural, emotional and cognitive engagement.